Study the Effect of Humidity Variable on the Patient with Jaundice Stay Period inside the Incubator - Auns Q. Al-Neami1, Yasser Ibrahim2, Husam Yahya Naser3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, a DHT22 sensor was used based on the Arduino platform for the purpose of measuring and monitoring the humidity in the incubator during the period of treatment of new-borns suffering from jaundice. This system was adopted because it has a range of advantages that make it accessible to researchers as it does not need a highly experienced or specialist operator because it is easy to use as well as low-cost. The use of this system provides continuous and real monitoring of the humidity in the incubator to help determine the effect of humidity on the treatment period of the child with jaundice in the hospital. In addition, checking the level in the humidity error and the difference between the required moisture and the actual moisture recorded.